1990
DOI: 10.1002/jcp.1041440218
|View full text |Cite
|
Sign up to set email alerts
|

Altered regulation of platelet‐derived growth factor A‐chain and c‐fos gene expression in senescent progeria fibroblasts

Abstract: The study of human genetic disorders known as premature aging syndromes may provide insight into the mechanisms of cellular senescence. These diseases are clinically characterized by the premature onset and accelerated progression of numerous features normally associated with human aging. Previous studies have indicated that fibroblasts derived from premature aging syndrome patients have in vitro growth properties similar to senescent fibroblasts from normal individuals. As an initial approach to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 110 publications
(116 reference statements)
1
9
0
1
Order By: Relevance
“…This reduction is primarily due to decreased transcription of the c-fos gene as previously reported for different fibroblast lines (Seshadri and Campisi 1990;Winkles et al 1990), but is likely due also to altered modification of Fos within aged fibroblasts, since although old fibroblasts express Fos protein, none of this protein is detectable in a form capable of binding a consensus AP-1 site (Fig. 6).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This reduction is primarily due to decreased transcription of the c-fos gene as previously reported for different fibroblast lines (Seshadri and Campisi 1990;Winkles et al 1990), but is likely due also to altered modification of Fos within aged fibroblasts, since although old fibroblasts express Fos protein, none of this protein is detectable in a form capable of binding a consensus AP-1 site (Fig. 6).…”
Section: Discussionsupporting
confidence: 68%
“…These include c-fos (Holt et al 1986;Nishikura and Murray 1987;Riabowol et al 1988;Kovary and Bravo 1991), c-HRas (Mulcahy et al 1985), c-myc (Armelin et al 1984;Heikkila et al 1987;Holt et al 1988), and c-raf-1 (Kolch et al 1991). However, expression of these genes is not appreciably changed in senescent cells (Rittling et al 1986), with the exception of c-fos (Seshadri and Campisi 1990;Winkles et al 1990;Riabowol et al 1992). Previous work has suggested that senescent cells are unable to pass through the GI phase of the cell cycle (Macieira-Coelho and Taboury 1982;Cristofalo et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…PCR was performed for 35 cycles using the following conditions: denaturing at 94jC for 30 s, annealing at 66jC for 30 s, and extension at 72jC for 30 s. For Southern blotting, genomic DNA was isolated as described above and then digested with EcoRI and SalI. Hybridization analysis was conducted as described (16). Targeted ES clones were injected into C57BL/6 blastocysts to generate chimeras.…”
Section: Methodsmentioning
confidence: 99%
“…For the majority of cellular genes examined, changes in expression have been found to be minimal. For example, the expression of genes encoding actin, ornithine decarboxylase, c-Myc, pl05Rb, and Jun, among others (34,35,39,46,47,56), decreases by s50% as cells become senescent. In contrast, considerable changes in expression levels have been observed for a subset of growth-related genes such as those encoding insulin-like growth factor (IGF)-binding protein 3, cyclin D1, cdc2, cdk2, cyclin A, the A chain of platelet-derived growth factor, cyclin B, and Fos (2,10,23,31,34,38,48,(54)(55)(56).…”
mentioning
confidence: 99%